Comparison of different therapies for neonatal diabetes – glibenclamide vs insulin - Iberl, M (2012)
Gain-of-function mutations in the Kir6.2 and SUR subunits of the KATP channel are associated with neonatal diabetes (ND). I used a mouse model selectively expressing the Kir6.2-V59M mutation in pancreatic β-cells (inducible iβ-V59M) to compare the effects of sulphonylurea and insulin therapy on neonatal diabetes. Gene expression was induced in adulthood, which caused severe hyperglycaemia and resulted in a major decrease in insulin content, pancreatic β-cell area, pancreatic islet number, single islet size and total islet area. Insulin secretion and glucose tolerance were also severely impaired. To determine if the preservation of physiological blood glucose levels (~4mM) alone is sufficient to prevent these effects, or if the closure of the KATP channel is also required, induced iβ-V59M mice were implanted with insulin pellets or a high-dose glibenclamide pellet. Insulin therapy restored blood glucose levels but failed to fully preserve pancreatic islet and β-cell morphology and function. Conversely, glibenclamide therapy reduced elevated blood glucose concentrations down to a physiological range and maintained pancreatic islet and β-cell morphology and function. These findings have implications for treatment of human patients suffering from neonatal diabetes.